ANALISIS DAN PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM PADA SMA NEGERI 6 KOTA JAMBI - Suprapto, Cahyo Adi; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2017)
The goals of the thesis were to design a system that supports the documentation anddissemination of better knowledge to all educators and education personnel in SMAN 6 Kota Jambi. Howto design a knowledge management system that can transfer knowledge from documents, guides andsolutions of cases that have occurred so that it can be distributed to all teachers and educationalpersonnel equally. Factors to be studied are the main components of Knowledge Management (KM) iepeople, process, and technology and for the design of Knowledge Management System using knowledgeroadmap theory from Tiwana. The data in this research is taken from interview with Headmaster,Teacher and IT Staff at SMAN 6 Kota Jambi. The tool used is Alfrsco Community Edition. With thisresearch is expected to assist in documenting and disseminating knowledge in SMAN 6 Kota Jambi